Fluid Dynamics Of Oscillatory Flow Across Parallel-Plates In Standing-Wave Thermoacoustic System With Two Different Operation Frequencies - Mohd Saat, Fatimah Al Zahrah; Almukhtar Allafi, Waleed; Mao, Xiaoan (Elsevier B.V., 2021)
Thermoacoustic system is one of the alternative technologies that provides green working principles but the lack of understanding of the complex fluid flow and energy transfer interactions within structures inside the system is leading to difficulty in accurate analysis related to the system. This study presents fluid dynamic investigation of vortex shedding and velocity profile of an oscillatory flow across a parallel-plate structure inside a standing-wave thermoacoustic system by using a two-dimensional ANSYS FLUENT CFD (computational fluid dynamics) of SST k-x turbulence model. The model was validated using experimental data and theoretical solution. Two different operating frequencies of 14.2 Hz and 23.6 Hz were investigated with drive ratios (defined as maximum pressure amplitude to mean pressure) from 0.3% up to 3%. The results revealed that velocity profiles and boundary layers within the area of parallel-plate stack changes with time and the changes followed the cyclic travel of vortex across the structure. Two layers of vortex formed near the surface of the solid structure. These layers, known as the main and secondary vortex layers, change with the cyclic flow, and are affecting the shape of velocity profiles within the channel. The appearance of an ‘m’ shape, a ‘slug’ shape and a ‘parabolic’ shape velocity profiles are also depending on the flow amplitude (drive ratio) and flow frequency. The ‘parabolic’ velocity profile is only found for a certain moment of flow with thick boundary layer. The results indicated that fully developed flow may not be likely for cases presented in this paper. Hence care should be exercised in the use of equations during the analysis of thermoacoustic system. As the parallel-plate structure is usually an important structure of the system, a proper understanding of the dynamics of flow within this structure is crucial. These findings are expected to give better insight for future design of thermoacoustic system.